Pengaruh Model Pembelajaran Inquiry Terhadap Hasil Belajar Teknik Dasar Passing Sepakbola di SMAN 1 Rengasdengklok Kabupaten Karawang - Mochamad Iqbal Maulana; Abduloh Abduloh; Astri Ayu Irawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
In order to improve students' football passing skills in physical education learning, treatment is needed that can improve students' skills in learning, one of which is through the inquiry learning model. The inquiry learning model is a learning that is strung together which focuses on the process of critical thinking and analysis to get their own answers to a problem. The purpose of this study was to find out how much influence the inquiry learning model has on the learning outcomes of football passing at SMAN 1 Rengasdengklok. The method used in this study is experimental. Research design One-Group Pretest-Posttest Design. The population and sample in this study were class XII students of SMAN 1 Rengasdengklok with a sample of 110 people. The instrument used in this research is the football passing test. Data analysis was performed using quantitative descriptive data analysis techniques. The research instrument used was the football passing test which included: prefix, imposition, follow-up movement, and results. This study uses statistical analysis, namely the normality test, homogeneity test and hypothesis testing. The results showed that there was an increase in the learning outcomes of passing football by 2.9%. From the results of data analysis, a low score was obtained from the level of students' passing ability from 110 samples, namely 0% or 0 students, while there was an average value of 8% or 8 students with moderate criteria. The dominant score obtained by students of SMAN 1 Rengasdengklok is at a high criterion level with a total of 50% or 50 students and with very high criteria, namely a total of 52% or 52 students. Obtained Mean = 14.682, Standard Deviation = 15.537, t = 9.911, df = 109, and Sig. (2-tailed) = < 0.001. From the output in the table above, the Paired Samples Test table is the main table of the output which shows the results of the tests carried out. This can be seen from the significance value (2-tailed) in the table. The significance value (2-tailed) of this case example is <0.001 (p <0.05). So that the results of the initial test and the final test experienced significant (meaningful) changes. Based on the descriptive statistics of the pre-test and post-test, it is proven that the final test is higher. It can be concluded that the use of the inquiry learning model has an influence on the learning outcomes of passing football for class XII students of SMAN 1 Rengasdengklok.